Five subglacial lakes and one of the Antarctica's thickest ice covers newly determined by radio echo sounding over the Vostok DomeC region - L. Cafarella; S. Urbini; C. Bianchi; A. Zirizzotti; I. Tabacco; A. Forieri (Norsk polarinstitutt, 2006)
Radio echo sounding (RES) measurements were collected from 1995 to 2003 during Italian Antarctic expeditions over the Vostok-Dome C region. The data collected allow for the reconstruction of a bedrock elevation map between the Belgica Highlands and the Aurora Subglacial Basin (112.0° - 124.0° E; 74.0° - 78.0° S). Moreover, analysis of the RES data has revealed one of the thickest ice covers in Antarctica (4755 ± 16 m; 118.321° E, 76.059° S) as well as five new subglacial lakes.